Implication of Change Management on Organizational Effectiveness - Sunday Mose, Okebaram (International Journal of Scientific Research and Management (IJSRM), 2015)
In every organization change occurred to be a phenomenon, a process and procedure of doing things that is influenced by the dynamic of the environment. The ability of the organization to manage these change indicate its agility, persistence to survival and in other words enable them to attain their objectives. Thus this study major thrust objectives includes: to ascertain the impact of change management on organizational effectiveness, to identify the challenges facing change management in organization and to determine extent the role of the actors in change management implementation promotes organizational effectiveness. Survey research design was adopted whereby questionnaire was administered to the respondents that enable the researcher to collect data to validate the assertion. A selected sample of 212 formed the population representative of the three studied organization. Then percentage table and Z-test statistical tool were used in presentation and test of hypotheses with the aid of SPSS. However, the study found that there is significance impact of change management on organizational effectiveness and that cultural and perceptional barriers are challenges facing change management in organization. Finally, that the role of the actors in change management implementation to a large extent promotes organizational effectiveness. The study recommends that the organization in order to embrace appropriate management of change should build-up potential change agents who can effortlessly exercise their capability, agility and resilience to adapt to change with less resistance etc.